2021
DOI: 10.1101/2021.04.27.441650
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Microglial ablation does not affect opioid-induced hyperalgesia in rodents

Abstract: Opioids are the frontline analgesics in pain management. However, chronic use of opioid analgesics causes paradoxical pain that contributes to the decrease of their efficacy in pain control and the escalation of dose in long-term management of pain. The underling pathogenic mechanism is not well understood. Microglia have been commonly thought to play a critical role in the expression of opioid-induced hyperalgesia (OIH) in animal models. We performed microglial ablation experiments using either a genetic (CD1… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 39 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…Microglia were suggested to modulate neuronal activity via BDNF during OIH expression 11 . However, other studies raise questions about the role of microglia 4, 12 . Astrogliosis is associated with various chronic pain conditions, including OIH models, but its pathogenic contribution has not been tested conclusively 9, 16 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Microglia were suggested to modulate neuronal activity via BDNF during OIH expression 11 . However, other studies raise questions about the role of microglia 4, 12 . Astrogliosis is associated with various chronic pain conditions, including OIH models, but its pathogenic contribution has not been tested conclusively 9, 16 .…”
Section: Discussionmentioning
confidence: 99%
“…1A-1B), consistent with previous observations 35,36 . A critical role of microglia in OIH was proposed in an early study 11 , but inconsistent findings were reported later 4,12 . In this study, we aimed to examine the potential role of reactive astrocytes in OIH development.…”
Section: Reactive Astrocytes Play Essential Role In Oih Expression An...mentioning
confidence: 99%
See 1 more Smart Citation